ON ONE APPROXIMATION METHOD OF THE APPROACH SOLVING OF VOLTERRA LINEAR INTEGRAL EQUATIONS - Федак, Іван Васильович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
One new method of the approach solving of Volterra second kin linear integral equations have proposed.